2021
DOI: 10.1038/s41598-021-89084-9
|View full text |Cite
|
Sign up to set email alerts
|

Dynamic miRNA changes during the process of epileptogenesis in an infantile and adult-onset model

Abstract: Temporal lobe epilepsy (TLE) is the most common epilepsy type. TLE onset in infancy aggravates features like severity, drug responsiveness, or development of comorbidities. These aggravations may arise from altered micro RNA (miRNA) expression specific to the early onset of the disease. Although the miRNA involvement in TLE is widely studied, the relationship between the onset-age and miRNA expression has not been addressed. Here, we investigated the miRNA profile of infantile and adult-onset TLE in rats combi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
12
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(14 citation statements)
references
References 67 publications
1
12
1
Order By: Relevance
“…Together, these results indicate that increased activity leads to increases and decreases in specific NSPs. Decreased NSPs may arise by decreasing transcript levels ( Raab-Graham and Niere, 2017 ; Dong et al, 2020 ), for instance, downstream of activity-induced expression of transcriptional repressors ( Ashok et al, 2020 ; Dong et al, 2020 ), by miRNA-mediated mechanisms ( Henshall et al, 2016 ; Bencurova et al, 2021 ; Zolboot et al, 2021 ) or by activity-induced degradation of NSPs. Recent studies identified a neuronal membrane-associated proteosome that degrades activity-induced NSPs ( Ramachandran and Margolis, 2017 ; Ramachandran et al, 2018 ; He et al, 2022 ) and is required for behavioral plasticity ( He et al, 2022 ).…”
Section: Discussionmentioning
confidence: 99%
“…Together, these results indicate that increased activity leads to increases and decreases in specific NSPs. Decreased NSPs may arise by decreasing transcript levels ( Raab-Graham and Niere, 2017 ; Dong et al, 2020 ), for instance, downstream of activity-induced expression of transcriptional repressors ( Ashok et al, 2020 ; Dong et al, 2020 ), by miRNA-mediated mechanisms ( Henshall et al, 2016 ; Bencurova et al, 2021 ; Zolboot et al, 2021 ) or by activity-induced degradation of NSPs. Recent studies identified a neuronal membrane-associated proteosome that degrades activity-induced NSPs ( Ramachandran and Margolis, 2017 ; Ramachandran et al, 2018 ; He et al, 2022 ) and is required for behavioral plasticity ( He et al, 2022 ).…”
Section: Discussionmentioning
confidence: 99%
“…Notably, altered levels of miR-335-5p appear to vary between models, consistent with temporally-and activitycontrolled miRNA expression. Indeed, miR-335-5p levels were upregulated in the hippocampus in several rodent models of TLE (34)(35)(36), butdownregulation has also been reported (33,37,38). Levels of miR-335-5p were downregulated in resected hippocampal tissue from people with TLE with hippocampal sclerosis (34).…”
Section: Discussionmentioning
confidence: 91%
“…Previous studies have demonstrated that the expression of certain miRNAs shows dramatic temporal changes as pathologic condition progresses [ 69 , 70 , 71 ]. Furthermore, the expression of a certain miRNA can be also bidirectional depending on the intensity of the same stimulation.…”
Section: Discussionmentioning
confidence: 99%